Chemical Interactions in Reinforced Concrete Exposed at a Tropical Marine Environment - Mendoza Rangel, José Manuel; Castro Borges, Pedro; Quintana Owen, Patricia; Balancan Zapata, Mercedes; Cabrera Madrid, Jesús Alejandro (2015)
Prediction of concrete structure behavior is complicated by diverse factors, including interaction between elements and concrete compounds, chlorides diffusion through concrete, and compounds formed by corrosion of steel reinforcement. These factors were evaluated in concrete test cylinders exposed to a tropical marine environment since 1993 (during 126 months). Electrochemical, chlorides profile, scanning electron microscope, and energy-dispersive X-ray spectrophotometry analyses were done and results compared. This suite of analytical methods accurately characterized reinforced concrete condition and generated data useful in developing prediction models of corrosion in concrete structures.